2017
DOI: 10.1007/s40962-017-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Modification Level Assessment in Sr-Modified Aluminium Alloys

Abstract: One way to improve the mechanical properties of Al-Si alloys is to add chemical modifiers that affect the microstructure of the cast components. Small amounts of Sr cause the modification of the eutectic Si particles from a coarse plate-like morphology into a fine fibrous one. This study sets out to analyse the effects of chemical modification on an Al-7%Si-0.3%Mg foundry alloy treated with Sr, ranging from 62 to 820 ppm. Assessment of modification level was evaluated by both thermal analysis technique and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Thus, it can be inferred that the concentration of Sr in the melt had a critical value of ~0.012% (to have an effect on modification of the eutectic Si phase), which is very close to the value (equal to 0.01%) given by Fortini et al [16]. Zarif et al [15] also pointed out that only 50 ppm is good enough to alter the morphology of Si.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, it can be inferred that the concentration of Sr in the melt had a critical value of ~0.012% (to have an effect on modification of the eutectic Si phase), which is very close to the value (equal to 0.01%) given by Fortini et al [16]. Zarif et al [15] also pointed out that only 50 ppm is good enough to alter the morphology of Si.…”
Section: Resultssupporting
confidence: 78%
“…Thus, to neutralize or offset the harmful effects of some trace elements, it is necessary to add larger amounts of Sr. However, an excessive amount of Sr forms a detrimental Al 2 Si 2 Sr phase [13,14,15], and frequently gives rise to increased hydrogen content in the melt [16,17,18]. Excess Sr can also initiate structural looseness and performance deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that porosity was increased with increased Sr and pores were associated with intermetallics. Barrirero [11] and Fortini [12] also found similar results. Nampoothiri [13] claimed that Sr was beneficial for eutectic modification, however, porosity was increased and localised particularly in the interdendritic region.…”
Section: Introductionsupporting
confidence: 66%
“…However, research has shown that the presence of small-size oxides helps to form nucleation site, especially those based on Al 3 Zr. Unlike the combination of Zr and Sc or Zr and Ti, the combination of Zr and Sr in aluminum alloys does not change the structure to non-dendritic and, at the same time, the given phases can bind Fe to them [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%